Analisa Faktor Sosial Ekonomi Petani Terhadap Produksi Usahatani Sayur Sayuran Di Desa Plaosan, Kecamatan Plaosan, Kabupaten Magetan - Martin Lukito; Ahadiati Rohmatiah (Universitas Merdeka Madiun, 2020)
Abstractâ€” The research objective was to partially and simultaneously analyze the influence of socio-economic factors of farmers (farmer age, education level, length of farming, number of family dependents, farm area, labor and capital) on farm production in Plaosan Village, Plaosan District, Magetan Regency. The population in this study were all vegetable farmers in Plaosan Village, Plaosan District, Magetan Regency. Data collection techniques using interviews and documentation. Meanwhile, the data analysis technique uses multiple linear regression analysis, hypothesis testing and determination analysis. The research findings (1) partially there is a significant influence on the variables of education, experience, land area, labor and capital on the production of vegetable farming in Plaosan Village, Plaosan District, Magetan Regency. Meanwhile, age and dependency variables influence the production of vegetable farming in Plaosan Village, Plaosan District, Magetan Regency; and (2) simultaneously there is a significant influence on the variables of age, education, experience, dependents, land area, labor and capital on the production of vegetable farming. Â Keywordsâ€”: socio-economy; farmers; farming.